Design of Discrete Frequency Coded Sequences using PSOCM for Target Detection with CAF - Rao, M. V. Nageswara; Rajeswari, K. Raja (Společnost pro radioelektronické inženýrství, 2011)
This paper presents the design of Discrete Frequency Coded (DFC) sequences with good auto correlation properties using Particle Swarm Optimization with Cauchy Mutation (PSOCM) technique. The crossambiguity function method is used to detect the stationary and moving targets in various target detection scenarios. The contour plots of the cross-ambiguity function are computed as a function of delay and Doppler frequency shift. The results are compared with DFC sequences of the sequence lengths N = 32 and N = 100.
Keywords: Discrete Frequency Coded Sequences; Cross Ambiguity Function; Particle Swarm Optimisation